Assessment of concentrations and normalized concentrations of variability in methotrexate concentrations between cycles - Škorić, Biljana; Jovanović, Marija; Miljković, Branislava; Kuzmanović, Miloš; Vučićević, Katarina (Archives of Pharmacy, 2022)
Administration of high dose methotrexate is common part of pediatric protocols for acute lymphoblastic leukemia and non-Hodking lymphoma. Methotrexate is used in doses 3 g/m2 or 5 g/m2 with the objective to achieve concentration that will ensure eradication of tumor cells with minimal toxic effect. The aim of this study is overview of drug concentration and assessment of therapy safety in relation to referent values. After obtaining Ethics committee approval at The Institute for mother and child Healthcare of Serbia “Dr Vukan Cupic” 50 pediatric patients with ALL or NHL were enrolled. Data on MTX usage was retrospectively collected. Concentrations and normalized concentrations per applied dose were compared with nonparametric tests in SPSS. MTX concentration mean (± sd) following administration of 3 g/m2 respectively 5 g/m2 doses were 19.72±6.62 mg/L respectively 34.73±17.13 at 24 h, 0.20±0.36 mg/L respectively 0.24±0.58 mg/L at 48h and 0.14±0.44 mg/L respectively 0.12±0.89 mg/L at 72h after start of the infusion. Statistically significant difference (p<0.001) is seen at 24h concentration between 3 g/m2 (mean rank 43.97) and 5 g/m2 (mean rank 103.36). In all other time points, there was no difference during comparison of concentrations nor normalized concentration, even though it is seen trend of higher values in 5 g/m2 group. Results of analysis show that administration of higher dose during simultaneous distribution and elimination phase leads to higher concentrations while during elimination phase this effect is less visible. However, administration of the high doses brings the risk of side effects due to reaching higher concentrations.